Well-posedness and global existence for a generalized Degasperis–Procesi equation. (April 2016) - Li, Jinlu; Yin, Zhaoyang
Abstract: We first establish the local existence and uniqueness of strong solutions for the Cauchy problem of a generalized Degasperis–Procesi equation in nonhomogeneous Besov spaces by using the Littlewood–Paley theory. Then, we prove the solution depends continuously on the initial data. Finally, we derive a blow-up criterion and present a global existence result for the equation.